ChemInform Abstract: Stereoselective Synthesis of (Sulfonimidoyl)cyclopropanes with (R)‐PhSO(NTs)CH2Cl and α, β‐Unsaturated Weinreb Amides: Tuning the of Selectivity Between C—Cl and C—S Bond Cleavage. Issue 27 (16th June 2016) - Shen, Xiao; Liu, Qinghe; Zhang, Wei; Hu, Jinbo
Abstract: The Weinreb amide group and the counter cation of the base are important for the selective C‐Cl bond cleavage of (R)‐PhSO(NTs)CH2 Cl.